Calibration of an electronic capacitance meter to pasture estimating in a precision agriculture project - Serrano, João M. (2012)
A three year project was established to demonstrate precision agriculture techniques and technology in pasture management. The standard method of assessing pasture and forage mass based on the cut of the whole forage contained in an area of the pasture requires great effort and expense to collect enough samples to accurately represent a pasture, and farmers are not willing to make this effort in day-to-day management of pastures. This paper describes the major steps required to accomplish the objective of calibrate an electronic capacitance meter (Grassmaster II) to indirect pasture estimating. The field tests for carrying out in different dates (different phenological stages), and in three dairy farms, represents the typical pastures in Alentejo region (grasses; leguminous; and bio divers mixture). For each sample were collecting 30 readings with the probe. In each field square, six geo-referenced pasture samples were collected from 1m2 areas where the pasture had been protected using exclosure cages. Regression techniques are used to relate the weight of the herbage (direct measurements) in kg of dry matter for hectare (DM) to the meter reading (CMR) of capacitance (indirect measurements). The estimation of dry matter of the herbage mass, in kg ha-1, based in capacitance was relatively good in two sites, with overall coefficients of determination of 0.87 and 0.90, respectively in bio divers mixture and grasses. In the leguminous the coefficients of determination obtained was 0.32. Further studies are desirable to confirm in more years these results and to verify the applicability of the technique to pastures of other plant species or multiple species.